Efficacy and safety of creatine phosphate sodium in the treatment of viral myocarditis: A systematic review and meta-analysis - Li Wang; Su-Fang Chen; Xi-Wei Huang; Zhi-Yang Wu; Qing-Mei Zhang (PLoS ONE, 2025)
Purpose To systematically evaluate the efficacy and safety of creatine phosphate sodium in the treatment of viral myocarditis, and to provide guidance for its clinical treatment. Methods We conducted a search of The Cochrane Library, PubMed, EMbase, and Web of Science databases to retrieve randomized controlled trials (RCTs) on the use of creatine phosphate sodium (CPS) in the treatment of viral myocarditis. The search was conducted up to April 2024. After screening the literature, extracting data, and evaluating the risk of bias in the included studies, we performed a meta-analysis using RevMan 5.4 and Stata17.0 statistical software. Results A total of 104 articles were retrieved, and 9 articles with a combined total of 1,116 patients were ultimately included in the meta-analysis. The results of the meta-analysis indicated that the overall efficacy rate in the phosphocreatine sodium treatment group was higher than that in the control group [RR = 1.22, 95%CI (1.15, 1.28), P<0.00001]. Furthermore, post-treatment levels of cardiac troponin I [MD = 0.1, 95%CI (0.07, 0.13), P<0.00001] and creatine kinase isoenzyme [MD = 9.43, 95%CI (7.04,11 .82), P<0 .00001] in the phosphocreatine treatment group were lower compared to those in the control group; both differences between groups were statistically significant. Additionally, there was no significant difference observed in adverse reaction incidence between the phosphocreatine sodium treatment group and conventional treatment group [RR = 1 .07, 95% CI (0 .68, 1 .67), P = O .77]. Conclusion Creatine phosphate sodium treatment can significantly improve the therapeutic effect of patients with viral myocarditis, and can reduce the levels of cTnI and CK-MB. Compared with conventional treatment, it has good safety.